A Severe Case of Drug-Induced Liver Injury after Gemcitabine Administration: A Highly Probable Causality Grading as Assessed by the Updated RUCAM Diagnostic Scoring System - Ilenia Mascherona; Caterina Maggioli; Maira Biggiogero; Oreste Mora; Lucia Marelli (Case Reports in Hepatology)
Gemcitabine is an antineoplastic drug used in several forms of advanced pancreatic, lung, breast, ovarian, and bladder cancer. Common side effects include bone marrow suppression, fatigue, diarrhea, nausea, gastrointestinal upset, rash, alopecia, and stomatitis. Transient serum enzyme elevations could be observed during therapy, but clinically significant acute liver injury has been rarely associated with its use. Few cases of acute liver injury have been reported in the literature. We reported the clinical case of a 73--year-old man who developed clinically significant acute hepatic injury after using gemcitabine. Possible causes, clinical presentation, and treatments are discussed. According to the updated RUCAM score, the case was rated 10 points and became a suspected drug-induced liver injury. Moreover, on the liver biopsy, there were histological findings of mild-to-moderate portal hepatitis, eosinophilia, bile duct injury, and mild perisinusoidal fibrosis, suggesting drug damage.